Men and Gender Equality: European Insights. (December 2014) - Scambor, Elli; Bergmann, Nadja; Wojnicka, Katarzyna; Belghiti-Mahut, Sophia; Hearn, Jeff; Holter, Øystein Gullvåg; Gärtner, Marc; Hrženjak, Majda; Scambor, Christian; White, Alan
In this article, some of the most important findings of the European research project The Role of Men in Gender Equality (2011–2012) are discussed. This project was the first systematic research study of all European Union member states and associated European Free Trade Association states regarding men and gender equality in the fields of education and paid labor, the involvement of men in care and domestic work responsibilities, men's health, gender-based violence, and men's participation in gender equality policy. The main objective of the study was to gain better knowledge on the role and positioning of men concerning gender equality. A number of themes were emphasized. First, as the situation of men and women in societies is relational, the role of men cannot be understood, if the role of women is neglected. Second, a perspective on men as a heterogeneous social group was chosen in order to gain insights into men's privileges as well as disadvantages according to class, ethnicity, disability, and other social indicators. This study shows that caring masculinity emerges as a central path forward, and one that is increasingly taken up in practice, together with women's increasing education and professional role, and rising expectations of gender-balanced task divisions. But there is a need for further research on the complex relationship between caring masculinities and gender-equal roles, including marginalized and unemployed groups and men who turn their frustrations against gender equality and women's new roles.